Septic cavernous sinus thrombophlebitis with formation of pseudoaneurysm in a 7-year-old child (Research, Society and Development, 2021)
Septic cavernous sinus thrombosis is a rare complication of infections involving paranasal sinuses and can lead to carotid cavernous aneurysm formation. Thus, the objective of this study was to describe the clinical case of a patient with internal carotid artery mycotic pseudoaneurysm secondary to a case of sphenoid sinusitis that evolved into a cavernous sinus syndrome. A seven-year-old female patient with a recent history of sphenoid sinusitis, showed signs of meningeal irritation, mental confusion and severe fever. Brain magnetic resonance imaging showed areas suggestive of acute infarctions secondary to vasculitis due to meningitis and thrombophlebitis of the left cavernous sinus, with the formation of an internal carotid artery pseudoaneurysm. The patient evolved with ptosis and complete paralysis of the left eye, associated with unilateral periorbital edema on the left, with visual turbidity. After antibiotic therapy for approximately five weeks, an endovascular procedure was performed, with a good clinical outcome. Therefore, this study highlights the importance of a high diagnostic suspicion to institute early treatment and increase survival, avoiding infant morbidity and mortality.